Pengaruh DNA terhadap Keputusan Pria: Selibat, Monogami, dan Poligami - Gusti Hadiatus Solehah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to explore the influence of biological factors, specifically DNA, on men's decisions regarding celibacy, monogamy, and polygamy. In this context, sexual and relationship decisions may be influenced by various genetic factors underlying individual behaviors and preferences. By analyzing genetic data from male samples who choose celibacy, monogamy, or polygamy, and collecting information about their social and psychological backgrounds, this research identifies genetic patterns that may be associated with tendencies toward one of these three options. Initial findings suggest that certain genetic variations may be related to relationship preferences and sexual behavior. This study provides new insights into how genetic factors can affect decisions related to relationship structures, with significant implications for further research on the interaction between biology and social behavior. The results of this research are expected to open up further dialogue regarding the role of genetics in determining human relationship dynamics.